Gelatinized sweet potato starches obtained at different preheating temperatures in a spray dryer - dos Santos, Thaís Paes Rodrigues [UNESP]; Franco, Célia Maria Landi [UNESP]; Leonel, Magali [UNESP] (Elsevier, 2020)
Native sweet potato starch was gelatinized at temperatures between 57 and 69 °C and then spray dried, to verify the changes caused by this process. The spray dried starch granules initially swelled with the increase in preheating temperature, displaying a larger diameter, but shrank upon colling. There was an increase in the gelatinization temperature and a decrease in the enthalpy change of the spray dried starches relative to those of native starch. Spray dried starch preheating at 69 °C showed highly reduced enthalpy change (80%) and relative crystallinity. Based on the parameters studied, the best preheating temperature was 67 °C. Under this condition, the starch can be applied in more viscous products that require a greater thickness, and with great process yield (65%). This study showed the feasibility of the application of this process to produce sweet potato starches with specific properties for different purposes in the food and non-food industries.
Keywords: Instant food; Pregelatinization; Spray dryer; Thermal properties